Development of An Oral Treatment with the PPAR-γ-Acting Cannabinoid VCE-003.2 Against the Inflammation-Driven Neuronal Deterioration in Experimental Parkinson’s Disease - Sonia Burgaz (Molecules, 2019)
In a recent study, we described the neuroprotective properties of VCE-003.2—an aminoquinone derivative of the non-psychotropic phytocannabinoid cannabigerol (CBG)—administered intraperitoneally (i.p.) in an inflammatory model of Parkinson’s disease (PD). We also demonstrated that these properties derive from its activity on the peroxisome proliferator-activated receptor-γ, in particular at a regulatory site within this receptor type. In the present study, we wanted to further confirm this neuroprotective potential using an oral lipid formulation of VCE-003.2, developed to facilitate the clinical development of this phytocannabinoid derivative. To this end, we evaluated VCE-003.2, administered orally at two doses (10 and 20 mg/kg), to mice subjected to unilateral intrastriatal injections of lipopolysaccharide (LPS), a classic model of inflammation-driven neuronal deterioration that recapitulates characteristics of PD. The administration of VCE-003.2 to these mice showed, as expected, poor activity in the different motor tests (rotarod, computer-aided actimeter) used in experimental parkinsonism, in general due to the lack of evident changes in these behaviors by LPS lesion. However, VCE-003.2, at 20 mg/kg, was highly active in improving the changes detected in LPS-lesioned mice in the cylinder rearing test. In addition, the histopathological analysis of the basal ganglia revealed a trend towards recovery at 20 mg/kg VCE-003.2 in the loss of tyrosine hydroxylase-containing nigrostriatal neurons, as well as a complete reduction in the elevated LAMP-1 immunolabeling (reflecting autophagy impairment) caused by LPS lesion. These effects were not seen at 10 mg/kg. This was associated with a partial reduction in the intense glial reactivity provoked by LPS in the substantia nigra, in particular the astroglial reactivity labeled with glial fibrillary acidic protein. The analysis using qPCR in the striatum of proinflammatory mediators, such as tumor necrosis factor-α, interleukin-1β, inducible nitric oxide synthase, and cyclooxygenase-2, showed that the marked elevations provoked by the LPS lesion tended to be, in general, attenuated by VCE-003.2 treatment, with the greatest effects normally found with the highest dose of 20 mg/kg. In summary, our data confirm the neuroprotective potential of an oral formulation of VCE-003.2 against neuronal injury in an in vivo model of PD based on neuroinflammation, and this study opens the possibility to further the development of oral VCE-003.2 in the clinic.